An overview of advanced material characterization techniques - Maleque, Md. Abdul; Kaiser, Mohammad Rejaul (2010)
Advanced material characterization (AMC) techniques are becoming popular because of continual innovation of different types of materials especially on nanomaterials. Moreover, advances in nanomaterials are attributed partially to the advances in materials characterization tools (also considered as analytical methods and tools) which has allowed nanomaterials to be observed and analyzed. In order to characterizethematerials, very sophisticated tools and techniques are required and specialized microscopes have already been evolved for the imaging of the nanoscale materials in the recent era. Among them some analytical tools are concentrated on imaging while others are for chemical analysis even sometimes they are integrated with each other. Besides these functions some techniques are concentrated on a specific character. This paper describes recently developed characterization techniques, their working principles and specialty in the field for advanced characterization of the materials. A case study on the morphology of advanced materials will also be discussed.